Interactional patterns of Chinese speakers of English in group interaction / Li Li - Li, Li (2015)
Group discussion as a speech event is commonly used by young adults in various contexts throughout the process of tertiary studies. With the increasing number of such young adults from China pursuing their tertiary level education in Malaysia, this study seeks to look at how these foreign language users of English carry out group discussions, specifically focusing on their interactional patterns. In particular, the aims of the study are: (1) to investigate the features and the politeness strategies used in opening and closing sequences in group discussions; (2) to explore the speech produced by the Chinese speakers and ascertain if it reflects the characteristics of some Chinese cultural values; and (3) to identify gender differences and similarities in naturally-occurring speech in the group interactions between male and female Chinese speakers. This study is conducted at two universities in Malaysia with a total number of 12 postgraduate Chinese students who are speakers of English as respondents. An analysis of the findings indicates that the sequential structures of the opening and closing sequences are distinct. They have some common features but differ in only some aspects such as sequential structure. The analysis also reveals that communication characteristics of the Chinese speakers such as being polite, implicit and listener-centred are evident in the opening and closing sequences. This implies that the Chinese cultural values still exist among the young adults. The gender difference in language use from this small sample group is noted to be wider in the same-gender group discussion as compared to the ones in the homogenous groups. This study has provided some insights into the interactional patterns of Chinese speakers of English in group discussions at tertiary level and although the findings cannot be generalizable, it is hoped that some aspects of the discourse features identified may be utilised to improve communication among such speakers in group.